2020
DOI: 10.1073/pnas.2005911117
|View full text |Cite
|
Sign up to set email alerts
|

Root angle modifications by the DRO1 homolog improve rice yields in saline paddy fields

Abstract: The root system architecture (RSA) of crops can affect their production, particularly in abiotic stress conditions, such as with drought, waterlogging, and salinity. Salinity is a growing problem worldwide that negatively impacts on crop productivity, and it is believed that yields could be improved if RSAs that enabled plants to avoid saline conditions were identified. Here, we have demonstrated, through the cloning and characterization of qSOR1 (quantitative trait locus for SOIL SURFACE ROOTING 1), that a sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
158
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(178 citation statements)
references
References 62 publications
(82 reference statements)
1
158
1
Order By: Relevance
“…Natural variations involving auxin signalling and gravitropism contributed to genetic diversity in the RGA During root formation and development processes, auxin regulates the gravitropic set-point angles by adjusting the magnitude of the anti-gravitropic offset component via TIR1/AFB-Aux/IAA-ARF-dependent auxin signalling within the gravity-sensing cells of the roots [82]. Some functional genes, DRO1, LAZY1 and qSOR1, which regulate root gravitropism by auxin signalling, are closely associated with RGA [7,41,83]. In this study, 153 DEGs involved in gravitropism, auxin signalling, and related pathways were detected by RNA-seq.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural variations involving auxin signalling and gravitropism contributed to genetic diversity in the RGA During root formation and development processes, auxin regulates the gravitropic set-point angles by adjusting the magnitude of the anti-gravitropic offset component via TIR1/AFB-Aux/IAA-ARF-dependent auxin signalling within the gravity-sensing cells of the roots [82]. Some functional genes, DRO1, LAZY1 and qSOR1, which regulate root gravitropism by auxin signalling, are closely associated with RGA [7,41,83]. In this study, 153 DEGs involved in gravitropism, auxin signalling, and related pathways were detected by RNA-seq.…”
Section: Discussionmentioning
confidence: 99%
“…Natural variation of the RGA has been reported, but the genetic basis for this variation is largely unknown [9,10,61,66]. Introgression lines in rice demonstrated that combinations of allelic variations in qSOR1 and DRO1 controlled the RGA in rice [83]. To date, little is known about genetic variation in apple RGAs.…”
Section: Discussionmentioning
confidence: 99%
“…Its expression is negatively regulated by auxin and the encoded protein helps mediate root tip cell elongations related to asymmetrical root growth and the downward bending of the root in response to gravity [4]. A previous study con rmed that qSOR1, which is a DRO1 homologue, is also negatively regulated by auxin, and is predominantly expressed in root columella cells to in uence root gravitropic responses [20]. All of these genes are potential targets for root system architecture (RSA)-related breeding.…”
Section: Introductionmentioning
confidence: 99%
“…The Dro1-NIL, developed by Uga et al 16 , has a relatively deep RGA with the combination of functional alleles of both DRO1 and qSOR1. The qsor1-NIL, developed by Kitomi et al 17 , has a shallower RGA than IR64, with the combination of nonfunctional alleles of both DRO1 and qSOR1. We hypothesize that P-dipping, creating the P hotspot at the soil surface, will have a positive interaction with the shallow root system in rice.…”
Section: Introductionmentioning
confidence: 99%